Toxoplasma Uveitis - Mildre Mercedes Vidal del Río; Gabriela Alexandra Villacis Paredes; Karen Daniela Salazar Pullutacsi; Génesis Camila Romero Paredes (Medisur)
Toxoplasma uveitis is an infection caused by the parasite, Toxoplasma gondii, whose definitive host is cats. Most of the patients are asymptomatic, however, among the main ophthalmological clinical manifestations, blurred vision or loss of vision stands out, in addition to "mobile flies" described by the patient. The diagnosis is purely clinical, with the help of complementary tests to verify the presence of the parasite. Treatment is based on a classic therapy of pyrimethamine and sulfadiazine plus corticosteroids. The objective of this bibliographic review is to delve into the pathophysiology, diagnosis and treatment of uveitis produced by Toxoplasma gondii in order to reduce the prevalence of this disease. A bibliographic review was carried out in the Scopus, Cochrane Library, Web of Science, PubMed, Scielo and Embase databases. The publication period of the articles established was from January 1, 2017 to December 31, 2022. 54 articles were found to which the exclusion criteria were applied and 36 studies were excluded, for this reason they were included in the study. 18 articles. Toxoplasma uveitis is very common, and for this reason it is extremely important to publicize the etiology of this disease and how to prevent it, since having knowledge of the risk factors is essential to avoid this pathology.